Risk factor analysis for neonatal lamb mortality in Malpura sheep - SWARNKAR, C P; GOWANE, G R; PRINCE, L L L; SONAWANE, G G (The Indian Journal of Animal Sciences, 2019)
The magnitude of risk for neonatal mortality (NM) due to non-genetic factors was assessed using data on 5,722 Malpura lambs born during 1991–2016 at ICAR-Central Sheep and Wool Research Institute, Avikanagar, Rajasthan. The association of non-genetic factors influencing lamb mortality was obtained by odds ratio (OR). The overall annual NM was 4.07% with around 3 times higher in hebdomadal (3.15%) than post-hebdomadal (0.93%) phase. In comparison to lambs with >3.50 kg birth weight, the OR varied from 2.03 (birth weight 3.01–3.50 kg) to 19.29 (birth weight